2005
DOI: 10.1021/ac050286w
|View full text |Cite
|
Sign up to set email alerts
|

Wafer-Scale Fabrication of Polymer-Based Microdevices via Injection Molding and Photolithographic Micropatterning Protocols

Abstract: Because of their broad applications in biomedical analysis, integrated, polymer-based microdevices incorporating micropatterned metallic and insulating layers are significant in contemporary research. In this study, micropatterns for temperature sensing and microelectrode sets for electroanalysis have been implemented on an injection-molded thin polymer membrane by employing conventional semiconductor processing techniques (i.e., standard photolithographic methods). Cyclic olefin copolymer (COC) is chosen as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Using COC, Ahn's group developed a biochip for blood typing (Kim et al 2006) while Bhattacharyya and Klapperich (2006) fabricated a device for purification of nucleic acids. Esch et al (2003) studied the effects of different embossing masters on COC microfluidic devices while Lee et al (2005) reported fabrication of COC devices in the wafer scale. Craighead's group employed COC chips for protein separation and for interfacing with a mass spectrometer Yang et al 2005) while Kirby et al studied the zeta potential of COC microchannels (Mela et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Using COC, Ahn's group developed a biochip for blood typing (Kim et al 2006) while Bhattacharyya and Klapperich (2006) fabricated a device for purification of nucleic acids. Esch et al (2003) studied the effects of different embossing masters on COC microfluidic devices while Lee et al (2005) reported fabrication of COC devices in the wafer scale. Craighead's group employed COC chips for protein separation and for interfacing with a mass spectrometer Yang et al 2005) while Kirby et al studied the zeta potential of COC microchannels (Mela et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In the experiments, performed by Lee et al (2005), it was noticed that the gold adhesion to the COP substrate was better than when using a typical pre-adhesive layer (usually Cr or Ti). The lack of an adhesion layer is an advantage especially when fabricating microelectrodes, since it eliminates the need of a passivation layer to protect the edges of the electrode that expose the adhesion layer to the solution.…”
Section: Injection Mouldingmentioning
confidence: 99%
“…Whereas, low temperature co-fired ceramics (LTCC) are incompatible with the integration of polymeric membranes due to the high temperatures reached during sintering process [14]. In addition, polymer technology has other important advantages like an easy microfabrication of hermetically sealed three dimensional structures, chemical inertia against most acids and alkalis, the possibility to integrate conductive tracks and a good mechanical resistance [15][16][17][18]. In this way, these advantages allow the possibility to obtain robust and low cost microanalyzers of rapid prototyping and with low sample and reagents consumption by means of the monolithic integration of all components of the analytical process (pretreatment stages, microfluidics and detection system) on a single substrate [19].…”
Section: Introductionmentioning
confidence: 99%